(untitled) (Mustansiria Dental Journal, 2018)
Polishing of dental prostheses can cause a dangerous cycle of cross-contamination involving dentists, laboratory technicians, patients and auxiliary personnel. The aim of this study was to show the microbial contamination in the dental laboratory during the polishing procedure of complete dentures. For this purpose, 30 samples & 4 experiments were conducted. Experiment I - Determination of the contaminating complete maxillary dentures from plaque &from patient saliva . Experiment II- after disinfection of complete dentures Experiment III- determination of microorganism transferred During the polishing procedure, to the denture Experiment IV - The remaining microorganism in the lathe spindle Microbiological tests were conducted to detect the presence of bacteria. plates showing growth, colonies were observed and identified using Gram staining,. As a result viable organisms from patients denture before and after polishing & after disinfection were found Improper disinfection of the denture , using tab water with pumice powder allowed for the introduction of pathogens so The polishing of dental prostheses is a possible source of transmission of communicable diseases in the laboratory appropriate universal precautions must be followed to decrease the likelihood of cross contamination